The influence of Icelandic aggregate on modulus of elasticity of concrete - Friad Nadir Hamad 1982- (2022)
Aggregates are the most abundant component in concrete by quantity and have a significant impact on its qualities. Because natural aggregates deposits are a finite resource, it's critical to understand aggregate qualities and use them appropriately. Fifteen aggregate size fractions from seven quarries were examined for their properties. Compressive strength and modulus of elasticity were among the concrete parameters examined. The aggregates were also tested i.e. the moisture content in saturated surface dry conditions, porosity, and flakiness index. To successfully model the behavior of a structure, knowledge of locally obtainable materials utilized in manufacturing concrete is required. Iceland’s supply of concrete aggregates is mainly porous basalt rock. Experiments and experience with specific raw materials are used to develop design codes and performance models, which are not always applicable internationally. Validating algorithms and models to verify their applicability is consequently critical. The goal of this thesis is to provide better comprehension of material characteristics by utilizing Icelandic raw materials. The effects of aggregate type and porosity on concrete elasticity were studied. The main goal is to establish a link between aggregate porosity together with some other aggregate parameters and the elastic modulus of concrete. Freeze-thaw scaling is perhaps the most serious threat to concrete durability in Iceland today. Air entrainment agents are added to the concrete mix to meet this requirement; however, this reduces compressive strength by around 5 percent for every 1 percent of air entrainment. A supplementary goal of this project is to find out how increasing air content affects concrete's elastic modulus. Þekking á eiginleikum steinefnanna er oft nauðsynleg þegar segja á fyrir um hegðun steinsteypu í mannvirkjum sem eru gerð úr heimafengnum steinefnum. Á Íslandi er framboð á steinefnum í steinsteypu mestmegnis takmarkað við bergtegundina basalt. Prófanir á völdum steinefnum eru, ...